Solution
prove
Solution
Solution steps
Manipulating left side
Rewrite using trig identities
Use the basic trigonometric identity:
Use the Angle Difference identity:
Simplify
Simplify
Use the following trivial identity:
periodicity table with cycle:
Multiply:
Simplify
Use the following trivial identity:
periodicity table with cycle:
Apply rule
Apply the fraction rule:
Rewrite using trig identities
Use the basic trigonometric identity:
Simplify
Apply the fraction rule:
Apply rule
We showed that the two sides could take the same form
Popular Examples
prove sin(-x)-cos(-x)=-(sin(x)+cos(x))prove prove 1-(cos^2(u))/(1-sin(u))=-sin(u)prove prove sin^2(t)=(1-cos(2t))/2prove prove tan(15)=tan(45-30)prove prove sec(x)sin(2x)=2sin(x)prove
Frequently Asked Questions (FAQ)
Is sec(pi-x)=-sec(x) ?
The answer to whether sec(pi-x)=-sec(x) is True